The Role of School Principal as an Educator in Developing Teachers’ Pedagogical Competence in SMA Negeri 1 Koba, Central Bangka Regency - Sataroh, Sindy; Hasanah, Enung (International Journal of Educational Management and Innovation, 2025)
Teachers have a central role in the learning process in the classroom, where one of the competencies that must be possessed is pedagogical competence. This competency is important so that teachers can manage learning effectively, develop the potential; of students, understand learning models, prevent monotonous learning, design learning programs, understand the characteristics of students, and evaluate learning outcomes. The research aims to determine the role of principal as an educator in developing teachers’ pedagogical competence in SMA Negeri 1 Koba, Central Bangka Regency. The research method used is qualitative with research subjects of the principal, vice principal of the curriculum section, and five teachers. Data were collected through interview, observation, and documentation. Data were analyzed through the stages of collection, condensation, display, and conclusions drawing/verification. The results showed that the principal in SMA Negeri 1 Koba plays a essential role as an educator in improving teachers’ pedagogical competence through providing guidance, providing encouragement, providing direction, building a conducive atmosphere, providing opportunities, setting an example, providing advice, and conducting training. This role allows teachers to learn and develop, both directly and indirectly.